Examining the entanglement of cognition and sociomaterial world in students’ sociodramatic play - Eka Margianti Sagimin; Setiono Sugiharto; Anna Marietta da Silva (Studies in English Language and Education, 2026)
This study aims to investigate how adult EFL learners entangle with cognition and the sociomaterial world in a multimodal context, forming an interconnectedness among them all in the process of learning and acquiring English through sociodramatic play performance. Drawing on a multidisciplinary perspective, this study incorporates the notions of sociocognitive, somaesthetic, spatial repertoires, and artifact as multimodality into a unified assemblage. Ten English Literature students participated as actors in a sociodramatic play project. The objectives are: 1) to explore in what way(s) adult EFL learners entangle with cognition and sociomaterial world in a sociodramatic play; 2) to investigate how this entanglement contributes to the learners’ meaning-making during the learning process. A qualitative classroom ethnography methodology was adopted, using data collected through direct classroom observation, field notes, video recordings, and in-depth interviews. The findings show that EFL classrooms can transform the manifestation of learning through cognition and sociomaterial world into a meaning-making process, which scaffolds the learning and teaching of English through various modes in an assemblage. The findings indicate that all learners were able to stimulate their cognitive processes and embody these through body positioning, resulting in more effective dialogue production. The study foregrounds the importance of recognizing that language learning is not solely a cognitive process, but also involves the entanglement of cognition and the sociomaterial world as integral factors that support language acquisition and learning opportunities.